Durable proteo-hybrid vesicles for the extended functional lifetime of membrane proteins in bionanotechnology. Issue 73 (19th August 2016) - Khan, Sanobar; Li, Mengqiu; Muench, Stephen P.; Jeuken, Lars J. C.; Beales, Paul A.
Abstract : Significant enhancement of membrane protein functional durability is demonstrated when reconstituted in hybrid lipid–block copolymer vesicles compared to conventional proteoliposomes. Abstract : The full capabilities of membrane proteins in bionanotechnology can only be realised through improvements in their reconstitution environments that combine biocompatibility to support function and durability for long term stability. We demonstrate that hybrid vesicles composed of natural phospholipids and synthetic diblock copolymers have the potential to achieve these criteria.